Psychosocial Stress Over the Lifespan, Psychological Factors, and Cardiometabolic Risk in the Community. Issue 7 (September 2018) - Gebreab, Sirak Zenebe; Vandeleur, Caroline L.; Rudaz, Dominique; Strippoli, Marie-Pierre F.; Gholam-Rezaee, Mehdi; Castelao, Enrique; Lasserre, Aurélie M.; Glaus, Jennifer; Pistis, Giorgio; Kuehner, Christine; von Känel, Roland; Marques-Vidal, Pedro; et al.
ABSTRACT: Objective: The complex relationship between psychosocial stress over the lifetime, psychological factors, and cardiometabolic risk is still poorly understood. Accordingly, our aims were (1) to independently assess the associations between childhood adversity, life-event stress in remote (earlier than the last 5 years), and recent adulthood and cardiometabolic risk, and (2) to determine the role of psychological factors including personality, coping, and depression in these associations. Methods: The sample included 2674 adults, aged 35 to 66 years, randomly selected from urban area. Participants underwent a physical examination including the assessment of obesity markers, blood pressure, and blood lipid and glucose levels. Stress during adulthood was determined using the severity scores of 52 stressful life events. Information on adverse childhood experiences and major depressive disorders was collected using semistructured interviews, whereas personality traits and coping mechanisms were evaluated through questionnaires. Results: Both childhood adversity and stress in remote adulthood were associated with elevated body mass index (β [95% confidence interval CI] = 0.249 [0.029 to 0.468]; 0.020 [0.006 to 0.034]), waist circumference (β [95% CI] = 0.061 [0.024 to 0.099]; 0.08 [0.04 to 0.11]), and the global cardiometabolic risk score (β [95% CI] = 0.278 [0.017 to 0.540]; 0.017 [0.001 to 0.033]) after adjustment for sociodemographic, lifestyle, and psychological factors. In addition, childhood adversity was associated with low high density lipoprotein levels (β [95% CI] = −0.021 [−0.042 to 0.000]), as well as increased fat mass and systolic blood pressure levels (β [95% CI] = 0.506 [0.165 to 0.846]; 0.952 [0.165 to 1.740]) and stress in remote adulthood with apolipoprotein B levels (β [95% CI] = 0.607 [0.312 to 0.901]). Psychological factors did not account for these associations and were not effect modifiers. Conclusions: Our data demonstrate that psychosocial stress during childhood and remote adulthood favor adiposity and abnormal lipid metabolism. Abstract : Supplemental digital content is available in the text.